Experimental and numerical study on column-foundation connection through external socket - Ma, Haiying; Lai, Minghui; Shi, Xuefei; Cao, Zhen; Zhou, Junyong (Journal of Civil Engineering and Management, 2021)
In practice, bridge foundations and pier columns are usually constructed with cast-in-place concrete. Precast columns are currently widely used in highway bridges in China, which can save construction time and improve concrete quality. The connection between precast bridge columns and the foundation can affect how forces transfer from one to the other. This paper investigates using external sockets to form a connection between the bridge column and foundation. This method can accelerate the bridge construction time with the additional advantages of improving the orientation and creating a large erection tolerance. Two types of connections are presented and tested to investigate the behavior of the column-foundation connections and find a more suitable way to use external socket connections. The experimental results show that the column-foundation connection design satisfies the design requirements. The results also show that roughening the column surface within the external socket is more effective at connecting the column to the foundation when using an external socket compared to attaching a steel plate on the column. The experimental results are validated with a finite element analysis, resulting in a proposal regarding the column-foundation connection behavior as well as design recommendations for the external socket connection.